1997
DOI: 10.1074/jbc.272.14.8937
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes Direct Glycosyl Phosphatidylinositol-anchored Proteins to the Myelin Sheath in Glycosphingolipid-rich Complexes

Abstract: The myelin sheath synthesized by oligodendrocytes insulates central nervous system axons and is a specialized subdomain of the plasma membrane, containing a restricted pattern of proteins and lipids. Myelin is enriched in glycosphingolipids and cholesterol, a lipid environment favored by glycosylphosphatidylinositol (GPI)-anchored proteins, which associate with these lipids in detergent-insoluble complexes in many cell types. Since proteins regulating oligodendroglia-neuron interaction are largely unknown and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
127
1
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 70 publications
7
127
1
1
Order By: Relevance
“…The present report, as well as those by Kim et al (1995) and Krämer et al (1997), indicates that an apical-type transport machinery, reflected by detergent-insoluble rafts as described for model polarized cells, is present in the mature OLGs as well. The evidence presented here was derived from experiments in which the fate of the viral glycoproteins HA and VSVG was examined.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The present report, as well as those by Kim et al (1995) and Krämer et al (1997), indicates that an apical-type transport machinery, reflected by detergent-insoluble rafts as described for model polarized cells, is present in the mature OLGs as well. The evidence presented here was derived from experiments in which the fate of the viral glycoproteins HA and VSVG was examined.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, evidence was presented demonstrating that the presence or absence of galactosylceramide or sulfatide was of no consequence to PLP transport to the plasma membrane of Chinese hamster ovary cells transfected with PLP. Yet it has also been reported that the MAL proteolipid (Kim et al, 1995) and GPI-anchored proteins (Krämer et al, 1997) are present in detergent-insoluble, sphingolipid-containing vesicles in myelinating OLGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant with the cross-linking-dependent redistribution of MAG into the detergentinsoluble fraction, there are changes in the phosphorylation of specific proteins, including Fyn and Gβ1-2, which have been shown previously to reside in lipid rafts (Kramer et al, 1997;Kramer et al, 1999;Melkonian et al, 1999;Marta et al, 2003). Fyn is a member of the Src family of kinases and is associated with cell adhesion, migration, proliferation, differentiation, apoptosis and cytoskeletal rearrangements (Osterhout et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid rafts have an important role as platforms for the initiation of signal transduction by favoring specific protein-protein interactions (Simons and Toomre, 2000). Using biochemical criteria to identify proteins in rafts, it has been shown that in myelin the GPI-linked proteins NCAM-120 and contactin, the doubly acylated proteins Fyn and Lyn kinases, 2′,3′-cyclic nucleotide 3′-phosphodiesterase (CNP) and myelin oligodendrocyte glycoprotein (MOG) partition into rafts (Kim et al, 1995;Kramer et al, 1997;Kim and Pfeiffer, 1999;Kramer et al, 1999;Taylor et al, 2002), whereas MAG does not. Cross-linking of some proteins to either ligand or antibody can result in their enhanced partitioning into rafts and participation in early signaltransduction events (Simons and Toomre, 2000).…”
Section: Introductionmentioning
confidence: 99%